Pelaksanaan Pendidikan Prilaku Hidup Sehat Dalam Pemenuhan Indikator Sekolah Ramah Anak ? - Yuli Setiawan, M. Hery; Sufa, Feri Faila (Jambura Early Childhood Education Journal, 2022)
The aim of this study is to evaluate the implementation of healthy lifestyle education in the fulfillment of child-friendly school indicators at the Surakarta institution of early childhood education. The history of this research is the responsibility of schools in the city of Surakarta to obtain the title of child-friendly schools, which in many measures of child-friendly schools implies healthy living behaviors. Efforts in the collaboration to achieve the status of child-friendly kindergarten. Education for healthier lifestyles is crucial in achieving the fulfillment of children's rights and security. This method of analysis uses descriptive qualitative studies through questionnaires, interviews, and documentation to analyze the data. In addition to fulfilling children's rights and protecting children, which are the key objectives of child-friendly schools, the conclusion of the healthy living habits investigation has been well carried out and supports the fulfillment of child-friendly school indicators. Abstrak Tujuan penelitian ini adalah untuk mengevaluasi implementasi pendidikan gaya hidup sehat dalam pemenuhan indikator sekolah ramah anak di lingkungan PAUD Surakarta. Sejarah penelitian ini adalah tanggung jawab sekolah di kota Surakarta untuk mendapatkan predikat sekolah ramah anak, yang dalam banyak ukuran sekolah ramah anak mengandung arti perilaku hidup sehat. Upaya kolaborasi untuk mencapai status taman kanak-kanak ramah anak. Pendidikan untuk gaya hidup sehat sangat penting dalam mewujudkan pemenuhan hak dan keamanan anak. Metode analisis ini menggunakan studi deskriptif kualitatif melalui angket, wawancara, dan dokumentasi untuk menganalisis data. Selain pemenuhan hak anak dan perlindungan anak yang menjadi tujuan utama sekolah ramah anak, kesimpulan dari investigasi kebiasaan hidup sehat telah dilakukan dengan baik dan mendukung pemenuhan indikator sekolah ramah anak.